Polishing of transition metals
Patent Information
- Application Number
- CN202280045852.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-30
- Filing Date
- 2022-06-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-06-22
AI Technical Summary
另外,这种方法出现严重垫染色,尤其在中性到碱性pH条件下,以及差再现性
[0012] In the method of the present invention, the composition is advantageously used to polish microelectronic device substrates having a transition metal surface thereon. In some embodiments, the surface is selected from molybdenum-containing and ruthenium-containing films.
Smart Images

Figure CN117580975B_ABST
Abstract
Description
Technical Field
[0001] This invention generally relates to the field of microelectronic device manufacturing. More specifically, this invention relates to compositions and methods for chemical mechanical polishing of transition metals such as molybdenum, tungsten, cobalt, copper, and ruthenium. Background Technology
[0002] Microelectronic device wafers are used to form integrated circuits. A microelectronic device wafer comprises a substrate (e.g., silicon) in which regions are patterned for depositing different materials with insulating, conductive, or semi-conductive properties. To achieve proper patterning, excess material used to form layers on the substrate must be removed. Furthermore, to fabricate functional and reliable circuits, it is often important to prepare a flat or planar surface on the microelectronic wafer before subsequent processing. Therefore, it is necessary to planarize and / or polish certain surfaces of the microelectronic device wafer. Additionally, for optical devices, it may be necessary to smooth the surface for light transmission or to remove subsurface damage.
[0003] Chemical mechanical polishing or planarization (“CMP”) is a process that removes material from the surface of a microelectronic device wafer and planarizes and polishes the surface by combining physical processes (e.g., scraping) with chemical processes (e.g., oxidation or chelation). In its most basic form, CMP involves applying a slurry (e.g., a solution of abrasives and active chemicals) to a polishing pad to polish the surface of the microelectronic device wafer to achieve removal, planarization, and polishing. It is generally not desirable for the removal or polishing process to involve purely physical or purely chemical actions, but rather a synergistic combination of both to achieve rapid and uniform removal. In the fabrication of integrated circuits, CMP slurries should also be able to preferentially remove films including composite layers of metals and other materials, thereby producing highly flat surfaces for subsequent photolithography, patterning, etching, and thin-film processing. In conventional CMP operations, a substrate carrier or polishing head is mounted on a carrier assembly and placed in contact with a polishing pad within the CMP apparatus. The carrier assembly provides controlled pressure to the substrate, pressing the substrate onto the polishing pad. The pad is then moved relative to the substrate.
[0004] Molybdenum metal is used in interconnects, photomasks, and other applications in microelectronic devices. Typically, molybdenum is present in excess on these devices, requiring removal through polishing or grinding. Molybdenum polishing generally exhibits low removal rates when using silica abrasive compositions. High corrosion rates are often encountered when using oxidants (such as hydrogen peroxide).
[0005] Ruthenium is being considered as a replacement for Ta / TaN as a barrier material in copper interconnects, as a bottom electrode material in metal-insulator-metal capacitors, and as a next-generation pad and conductive metal. Ruthenium can be polished using abrasives along with oxidants; unfortunately, some of these compositions raise safety and toxicity concerns due to reaction products from this polishing process. Furthermore, ruthenium polishing is typically accompanied by low removal rates and high etching rates using conventional (colloidal) silica and iodate (i.e., oxidant) chemicals. Additionally, this method suffers from severe pad staining, especially under neutral to alkaline pH conditions, and poor reproducibility. In this regard, pad staining is believed to be a byproduct of ruthenium oxidation, which potentially produces insoluble substances that can ultimately lead to undesirable scratches on the ruthenium surface.
[0006] Therefore, there is still a need for novel and improved compositions and methods for polishing molybdenum and ruthenium without these difficulties. Summary of the Invention
[0007] In summary, the present invention provides compositions suitable for polishing transition metal surfaces commonly found on microelectronic devices. In one aspect, the present invention provides a composition comprising:
[0008] Liquid carrier;
[0009] Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina or amorphous silica to provide coated titanium dioxide abrasive particles;
[0010] The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and
[0011] Corrosion inhibitor.
[0012] In the method of the present invention, the composition is advantageously used to polish microelectronic device substrates having a transition metal surface thereon. In some embodiments, the surface is selected from molybdenum-containing and ruthenium-containing films. Attached Figure Description
[0013] Figure 1 This is a graph showing the etching rate (in angstroms per minute) of the molybdenum substrate versus the concentration of the corrosion inhibitor, with the etching rate represented by shaded bars. The name "SER" refers to the static etching rate (dot bar). This data corresponds to Example 4.
[0014] Figure 2 This refers to the surface finish of a molybdenum surface polished using the composition of the present invention. This data corresponds to Example 5.
[0015] Figure 3 This is a graph showing the removal rates (in angstroms per minute) for various abrasives and abrasive / oxidant combinations. Detailed Implementation
[0016] As used in this specification and the appended claims, unless expressly indicated otherwise, the singular forms “a,” “an,” and “the” include a plurality of indicators. As used in this specification and the appended claims, unless expressly indicated otherwise, the term “or” is generally used in its sense that it includes “and / or.”
[0017] The term "approximately" generally refers to a series of numerical values that are considered equivalent to the referenced value (e.g., having the same function or result). In many cases, the term "approximately" may include numerical values rounded to the nearest significant number.
[0018] The range of values represented by endpoints includes all values covered within the range (for example, 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, and 5).
[0019] The compositions of the present invention are suitable for use in CMP polishing compositions (i.e., slurries) containing transition metal materials. In one embodiment, these metals comprise ruthenium, rhodium, palladium, osmium, iridium, platinum, gold, silver, copper, and rhenium. In another embodiment, the metals comprise tungsten, cobalt, and copper, as well as oxides and nitrides of these metals. In yet another embodiment, the metals comprise ruthenium and molybdenum. Therefore, the present invention provides a composition comprising, in a first aspect,:
[0020] Liquid carrier;
[0021] Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina or amorphous silica to provide coated titanium dioxide abrasive particles;
[0022] The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and
[0023] Corrosion inhibitor.
[0024] In this invention, the coated titanium dioxide (TiO2) particles are widely commercially available. These coated titanium dioxide particles generally have an average diameter of about 50 to about 250 nm, about 100 to about 250 nm, about 50 nm to about 150 nm, or about 20 nm to about 50 nm. Coating these titanium dioxide particles with amorphous silica or alumina can be accomplished by known methods. See, for example, "Dense silica coating of titanium nanoparticles by seeded polymerization technique," Ahmed Mohamed El-Toni, Shu Yin, and Tsugio Sato. colloid and surface A Physical chemistry and engineering ( Colloids and Surfaces A Physicochemical and Engineering Aspects, Vol. 274, Nos. 1-3, February 15, 2006, pp. 229-233. Coating titanium dioxide with alumina (Al₂O₃) can be accomplished by the following gas-phase deposition methods: hydrolysis or decomposition of volatile substances; addition of oxides, hydroxides, or substances adsorbable onto the surface during pigment milling, resulting in a partial coating on the pigment surface; or precipitation of the coating from an aqueous solution onto suspended TiO₂ particles.
[0025] In one embodiment, the titanium dioxide abrasive particles are in rutile form. Generally, component b above (i.e., the coated titanium dioxide particles) mainly comprises titanium dioxide (together with the alumina or amorphous silicon coating); however, in addition to titanium dioxide, small amounts of dopants or materials may also be present in the titanium dioxide abrasive particles, for example, about 5% by weight or less, about 2% by weight or less, or about 1% by weight or less.
[0026] As described above, the compositions of the present invention comprise at least one organic corrosion inhibitor. Essentially, these organic corrosion inhibitors belong to the general category of surfactants. As used herein, the term "surfactant" refers to an organic compound that reduces the surface tension (or interfacial tension) between two liquids or between a liquid and a solid, and is typically an amphiphilic organic compound containing both a hydrophobic group (e.g., a hydrocarbon (e.g., an alkyl) "tail") and a hydrophilic group. In one embodiment, these surfactants or metal corrosion inhibitors are cationic surfactants. Cationic surfactants are essentially surface-active molecules having at least one positively charged moiety. In one embodiment, the cationic surfactant is selected from C6-C6. 18 Ammonium halides. (C6-C)18 "Regulator" refers to a surfactant that contains a certain number of carbon atoms and may include aliphatic and aromatic moieties. In another embodiment, the cationic surfactant is selected from C... 12 -C 18 Ammonium halides.
[0027] Exemplary cationic surfactants (corrosion inhibitors) include, but are not limited to, cetyltrimethylammonium bromide (CTAB) (also known as hexadecyltrimethylammonium bromide), hexadecyltrimethylammonium chloride (CTAC), heptadecanofluorooctane sulfonic acid, tetraethylammonium halide, stearyltrimethylammonium chloride, 4-(4-diethylaminophenylazo)-1-(4-nitrobenzyl)pyridine bromide, cetylpyridinium chloride monohydrate, benzalkonium chloride, benzalkonium bromide, benzyldimethyldodecylammonium chloride, benzyldimethylhexadecylammonium chloride, hexadecyltrimethylammonium bromide, dimethyl dioctadecylammonium chloride, dodecyltrimethylammonium chloride, didodecyldimethylammonium bromide, di(hydrogenated tallow)dimethylammonium chloride, tetraheptylammonium bromide, tetra(decyl)ammonium bromide and hydroxyphenylacetium bromide, dimethyl dioctadecylammonium chloride, dimethyl dihexadecylammonium bromide and di(hydrogenated tallow)dimethylammonium chloride. In one embodiment, the corrosion inhibitor / surfactant is selected from benzalkonium chloride and benzalkonium bromide.
[0028] These corrosion inhibitors / surfactants are typically present in amounts from about 0.0001 to about 5% by weight (based on the total weight of the composition) and are found to be necessary through empirical observation.
[0029] In the compositions of the present invention, the relative amount of coated titanium dioxide particles can be adjusted as needed based on the total weight of the composition for polishing specific transition metal surfaces. In some embodiments, the coated titanium dioxide particles are present in an amount of about 0.001 to about 5% by weight, or about 0.1 to about 1% by weight (based on the total weight of the composition). Any suitable amount of abrasive may be present in the polishing composition, depending on the surface being polished and other conditions used. In some embodiments, the abrasive is present in the polishing composition at a concentration of about 0.0005 wt.% or more, for example, about 0.001 wt.% or more, about 0.0025 wt.% or more, about 0.005 wt.% or more, about 0.01 wt.% or more, about 0.025 wt.% or more, or about 0.05 wt.% or more. More typically, the abrasive is present in the polishing composition at a concentration of about 0.001 wt.% or more, such as about 0.0025 wt.% or more, about 0.005 wt.% or more, about 0.01 wt.% or more, about 0.025 wt.% or more, or about 0.05 wt.% or more. Alternatively, the abrasive is present in the polishing composition at a concentration of about 30 wt.% or less, such as about 20 wt.% or less, about 10 wt.% or less, about 5 wt.% or less, about 1 wt.% or less, about 0.5 wt.% or less, about 0.1 wt.% or less, or about 0.05 wt.% or less. More typically, the abrasive is present in the polishing composition at a concentration of about 1 wt.% or less, such as about 0.5 wt.% or less, about 0.1 wt.% or less, or about 0.05 wt.% or less. Therefore, the abrasive may be present in the polishing composition in an amount defined by any two of the above endpoints.For example, the abrasive can be from about 0.0005 wt.% to about 10 wt.%, such as about 0.001 wt.% to about 10 wt.%, about 0.001 wt.% to about 1 wt.%, about 0.001 wt.% to about 0.5 wt.%, about 0.001 wt.% to about 0.1 wt.%, about 0.001 wt.% to about 0.05 wt.%, about 0.005 wt.% to about 10 wt.%, about 0.005 wt.% to about 1 wt.%, about 0.005 wt.% to about 0.5 wt.%, about 0.005 wt.% to about 0.1 wt.%, about 0.005 wt.%. The abrasive is present in the polishing composition at concentrations of about 0.05 wt.%, about 0.01 wt.%, about 10 wt.%, about 0.01 wt.%, about 1 wt.%, about 0.01 wt.%, about 0.5 wt.%, about 0.01 wt.%, about 0.1 wt.%, about 0.01 wt.%, about 0.05 wt.%, about 0.05 wt.%, about 10 wt.%, about 0.05 wt.%, about 0.05 wt.%, about 0.05 wt.%, about 0.05 wt.%, or about 0.05 wt.% to about 0.05 wt.%. In some embodiments, the abrasive is present in the polishing composition at a concentration of about 0.001 wt.% to about 1 wt.%.
[0030] In another embodiment, the composition of the present invention further comprises at least one oxidizing agent. As used herein, the term "oxidizing agent" refers to any chemical substance other than ambient air capable of oxidizing ruthenium to an oxidation state greater than +4. Exemplary lists of such oxidizing agents include, but are not limited to, peroxides (e.g., H₂O₂), periodic acid, oxone, bromate, bromate, hypobromite, chlorate, chlorite, hypochlorite, perchlorate, iodate, hypoiodate, periodate, cerium(IV) salts, permanganate, silver(III) salts, peracetic acid, organohalooxy compounds, monoperoxysulfate, monoperoxysulfite, monoperoxythiosulfate, monoperoxyphosphate, monoperoxypyrophosphate, and monoperoxyhypophosphate. Other oxidizing agents include hydrogen peroxide; other peroxides, such as salts and acids containing anions of peroxymonosulfate, perborate, perchlorate, periodate, persulfate, permanganate, and peracetate; and amine-N-oxides. Other examples include FeCl3, FeF3, Fe(NO3)3, Sr(NO3)2, COF3, MnF3, ozone, 2KHSO5·KHSO4·K7SO4, iodic acid, vanadium oxide (V), vanadium oxide (IV, V), ammonium vanadate, polyatomic ammonium salts (e.g., ammonium persulfate, ammonium chlorite (NH4ClO2), ammonium perchlorate (NH4ClO3), ammonium iodate (NH4IO3), ammonium nitrate (NH4NO3), ammonium perborate (NH4BO3), ammonium perchlorate (NH4ClO4), ammonium periodate (NH4IO4), ammonium persulfate ((NH4)2S2O8), ammonium hypochlorite (NH4ClO)), and ammonium tungstate ((NH4) 10H2(W2O7)), polyatomic sodium salts (e.g., sodium persulfate (Na2S2O8), sodium hypochlorite (NaClO), sodium perborate), polyatomic potassium salts (e.g., potassium iodate (KIO3), potassium permanganate (KMnO4), potassium persulfate, nitric acid (HNO3), potassium persulfate (K2S2O8), potassium hypochlorite (KClO), polyatomic tetramethylammonium salts (e.g., tetramethylammonium chlorite (N(CH3)4)ClO2), tetramethylammonium chlorate (N(CH3)4ClO3), tetramethylammonium iodate (N(CH3)4)IO3), tetramethylammonium perborate (N(CH3)4)BO3), tetramethylammonium perchlorate (N(CH3)4)ClO 4) Tetramethylammonium periodate ((N(CH3)4)IO4), tetramethylammonium persulfate ((N(CH3)4)S2O8)), polyatomic tetrabutylammonium salts (e.g., tetrabutylperoxymonosulfate), peroxymonosulfate, ferric nitrate (Fe(NO3)3), urea peroxide ((CO(NH2)2)H2O2), peracetic acid (CH3(CO)OOH), 1,4-benzoquinone, formone, dimethyl-1,4-benzoquinone, chloroquinone, alloxan, N-methylmorpholine N-oxide, trimethylamine N-oxide, and combinations thereof. Other examples of oxidants include perbromic acid, trifluoroperacetic acid tellurate, m-chloroperoxybenzoic acid, tert-butylhydroperoxide, benzoyl peroxide, potassium persulfate (e.g., DuPont), methyl ethyl ketone peroxide, acetone peroxide, ethyl hydrogen peroxide, and cumene hydrogen peroxide.
[0031] In one embodiment, the amount of oxidant based on the total weight of the composition is in the range of about 0.001 wt% to about 5 wt%, and in another embodiment it is in the range of about 0.001 wt% to about 2 wt%.
[0032] In some embodiments, the peroxide oxidant is used in conjunction with a Fe(II) or Fe(III) source (e.g., Fe(NO3)3 in the Fenton reaction), which generates hydroxyl radicals in situ as oxidants.
[0033] The compositions of the present invention may further include a pH stabilizer. Both organic and inorganic pH stabilizers may be used. Examples of inorganic pH stabilizers include phosphates, phthalates, bicarbonates, and silicates. Examples of organic pH stabilizers include amines, glycine, and N-cyclohexyl-2-aminoethanesulfonic acid. In some embodiments, the compositions of the present invention will have a pH of about 2 to about 5. For a given composition, if necessary, pH adjusters such as acetic acid, nitric acid, sulfuric acid, hydrochloric acid, and phosphoric acid may be used, or, to make the given composition more alkaline, pH adjusters such as KOH, tetramethylammonium hydroxide (TMAH), tetrabutylammonium hydroxide (TBAH), etc., may be used.
[0034] The composition may further include a biocidal agent, such as a fungicide. Examples of fungicides include tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, alkylbenzyldimethylammonium chloride and alkylbenzyldimethylammonium hydroxide, 3,5-dimethyltetrahydro-1,3,5,2H-thiadiazine-2-thione, 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one, sodium chlorite and sodium hypochlorite.
[0035] As described above, the composition includes a liquid carrier. The liquid carrier includes water (e.g., deionized water) and optionally further includes one or more water-miscible organic solvents. Examples of usable organic solvents include alcohols such as isopropanol, ethanol, 1-propanol, methanol, 1-hexanol, and the like; aldehydes such as acetaldehyde and the like; ketones such as acetone, diacetone alcohol, methyl ethyl ketone, and the like; esters such as ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate, and the like; ethers, including sulfoxides such as dimethyl sulfoxide (DMSO), tetrahydrofuran, dioxane, dimethyl diethylene glycol ether, and the like; amides such as N,N-dimethylformamide, dimethylimidazolidinedione, N-methylpyrrolidone, and the like; polyols and their derivatives such as ethylene glycol, glycerol, diethylene glycol, diethylene glycol monomethyl ether, and the like; and nitrogen-containing organic compounds such as acetonitrile, pentylamine, isopropylamine, imidazole, dimethylamine, and the like. In one embodiment, the liquid carrier is only water, i.e., no organic solvent is present.
[0036] In some embodiments, the compositions of the present invention consist of or are substantially composed of components a. and b. above and optional components stated herein. In some embodiments, the compositions are substantially free of oxidizing agents. As used herein, the phrase “substantially free of oxidizing agents” means a composition comprising less than about 1 ppm of oxidizing agent, such as less than about 100 ppb, less than about 10 ppb, less than about 1 ppb, less than about 100 ppt, less than about 10 ppt, or less than about 1 ppt. In some embodiments, the polishing compositions are free of oxidizing agents (i.e., below detectable levels).
[0037] The polishing process can be performed at temperatures ranging from approximately 15°C to approximately 100°C. Higher temperatures are expected to increase the polishing rate of molybdenum or ruthenium. In one embodiment, the temperature range is from approximately 25°C to approximately 65°C. One way to achieve higher temperatures is to preheat the slurry before it is supplied to the CMP apparatus.
[0038] Regarding the polishing pad, any type of polymer-based polishing pad can generally be used. Examples of polishing pads are based on polyurethane pads and chamois pads. The pad thickness can vary from 0.1 mm to 25 mm. The hardness of the chamois pad can vary from Asker C hardness 5 to Asker C hardness 95. The compressibility of the chamois pad can be from 0.1% to 40%. The pore size of the porous chamois pad can vary from 2 micrometers to 100 micrometers, wherein the size is in the range of 20 to 60 micrometers in one embodiment. The porous pad layer can have a backing layer of polyethylene terephthalate (PET) or foam or nonwoven material with a thickness between 30 micrometers and 25 mm.
[0039] In addition to porous pads, polyurethane pads can also be used. Examples of polyurethane-based pads include the D-100 pad from Gabor Microelectronics, and the IC and Suba series from Dow Electronic Materials. These pads have a Shore D-value ranging from 5 to 99. The porosity of these pads can vary from 0.1% to 40%. It should be noted that generally any other type of polymeric material can be used with the slurry. Besides porous pads, metal pads (e.g., cast iron, copper, tin), granite, or resin surfaces can also be used as pads.
[0040] Suitable apparatus for chemical mechanical polishing is commercially available. The method of the present invention generally involves mixing a slurry composition comprising the components described above, placing the dielectric substrate to be polished in a CMP apparatus having a rotating pad, and then performing chemical mechanical polishing using the slurry composition of the present invention. In this polishing method, at least some of the dielectric substrate surface is removed or scraped, thereby providing a suitably polished dielectric substrate.
[0041] Therefore, in another aspect, the present invention provides a method for chemically and mechanically polishing a substrate comprising a surface including at least one transition metal, the method comprising:
[0042] The substrate is brought into contact with the composition, the composition comprising:
[0043] Liquid carrier;
[0044] Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina or amorphous silica to provide coated titanium dioxide abrasive particles;
[0045] The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and
[0046] Corrosion inhibitor.
[0047] To move the composition relative to the substrate; and
[0048] The substrate is scraped to remove a portion of the surface containing the at least one transition metal.
[0049] Advantageously, the compositions and methods of the present invention exhibit significantly improved removal rates compared to conventional slurries, reaching or exceeding about 200% in some embodiments. Additionally, in some embodiments, the compositions and methods of the present invention demonstrate a molybdenum-to-thermal oxide selectivity of about 100:1 for polishing molybdenum-containing films and about 12:1 for ruthenium-containing films.
[0050] The compositions of the present invention can be readily formulated by simply adding the appropriate ingredients and mixing to a homogeneous state. The compositions can be readily formulated as single-serving formulations or as multi-part formulations mixed at or before the point of use. The concentration of the appropriate ingredients can vary widely over specific factors of the composition, i.e., further dilution or concentration, and it should be understood that the compositions described herein may vary and optionally comprise, consist of, or substantially consist of any combination of components consistent with this disclosure.
[0051] Therefore, in another aspect, the present invention provides a kit comprising components selected from a., b. and c., and any optional components as described above, in one or more containers for combination at the point of use.
[0052] Example
[0053] abbreviation:
[0054] DL = Detection Limit
[0055] CMP = Chemical Mechanical Planarization or Polishing
[0056] DIW = Deionized Water
[0057] SER = Static Etching Rate
[0058] CI = Corrosion Inhibitor (listed in quantity)
[0059] Partial A-molybdenum polishing
[0060] In this section A, all concentrations are expressed as a weight percentage unless otherwise indicated. Water is added to bring the composition to 100% by weight. Additionally, CMP experiments are performed using the procedures and experimental conditions given below. The data provided in the following examples were obtained by polishing 1.75” x 1.75” specimens cut from a blanket-reinforced molybdenum wafer. The thickness of the molybdenum film, measured using a profilometer, is... Upon receipt, the thickness was confirmed using a four-point resistance probe.
[0061] Various abrasives, including colloidal silica, are studied, which is considered a conventional abrasive for polishing molybdenum surfaces. The slurry used at the point of use (PoU) is prepared by diluting a slurry with a higher solids load. An appropriate weight of the initial slurry is mixed with deionized water (DIW) to achieve the desired solids load. For example, 10.6 g of silica slurry with an initial solids load of 47% by weight is stirred into 89.4 g of DIW to achieve a final particle content of 5% by weight. The operating pH is varied according to studies mentioned in the following examples. An aqueous solution of nitric acid and potassium hydroxide is used as a pH adjuster.
[0062] The CMP tool used for the polishing process was a Buehler Automet 250 with a platform size of 12”. The rotational speed was set to 150 RPM at the base and 30 RPM at the head. Throughout the study, a peristaltic slurry metering pump was set to dispense the polishing slurry at a rate of 30 ml / min. All processes used concentrically grooved Cabot D100 pads, except for testing the effect of pad variation on the removal rate. The polishing duration was set to 60 seconds. Pad temperature, mentioned anywhere herein, was measured using an IR thermometer during the polishing process.
[0063] The change in film thickness caused by polishing was determined by measuring the film thickness before and after polishing using a four-point resistance probe. The polishing non-uniformity observed from the change in film thickness of the polished sample is due to the non-uniform pressure distribution from the Böhler polishing machine. To address this non-uniformity, the removal rate was determined based on the film weight lost during the polishing process.
[0064] Example 1 (Samples A to F)
[0065] Mo specimens were polished using slurries A through F at an operating pH of 1.5 and a pressure of 4 psi. Two different classes of abrasives were used: silica and titanium dioxide. All abrasives were from different suppliers. These are 'single-abrasive' slurries, meaning that no oxidizing chemicals were introduced into these formulations. A pressure of 4 psi was used throughout these processes. The solids loading and corresponding removal rates for each slurry are listed in Table 1. It is evident from the values in the table that the titanium dioxide-dominant slurries produced the highest removal rates in all polishing processes in this group. The higher rate of slurry E, containing titanium dioxide particles with 410 nm APS, can be attributed to its larger particle size. However, the comparable rates observed by polishing in the presence of slurries F and G, containing titanium dioxide particles with 200 nm APS, are surprising. This higher removal rate is attributed to the surface modification of the titanium dioxide particles in these slurries. The novelty of this surface modification lies in the inorganic coating of transition metal oxides on the surface. This surface functionalization endows the titanium dioxide particles, which act as heterogeneous catalytic centers upon contact with the Mo surface, with catalytic activity. When a slurry containing these particles is used to polish a Mo surface, this behavior mimics the effect of CMP. This effect is sufficient to maintain the removal rate, and even sufficient to maintain a lower solids load as low as 1%.
[0066] Table 1: Removal rate data of abrasive slurry alone at operating pH 1.5
[0067]
[0068] Example 2
[0069] The Mo specimens were further polished using a 'single abrasive' slurry containing the unique titanium dioxide-coated particles described in Example 1, with the polishing time being a function of the operating pH. The operating pH varied between 1.5 and 13, maintaining a 5% solids load and a downpressure of 4 psi. Table 2 shows the Mo removal rates corresponding to each operating pH. The Mo removal rate was significantly highly dependent on the operating pH, with the most acidic slurry producing the highest removal rate. The presence of titanium dioxide abrasive had a more pronounced effect on pH compared to silica abrasive, as it exhibited a significantly higher removal rate. At this pH, the static etching rate (SER) of Mo was below the detection limit.
[0070] Table 2: Removal rate data of individual abrasive slurries at different operating pH levels
[0071]
[0072] Example 3
[0073] The Mo specimens were polished at a constant operating pH of 1.5 in the presence of slurry F. The performance of the slurry with different hardness values was investigated on different polishing pads. Table 2 shows the removal rates and corresponding hardness values associated with various pads. Hardness values were measured on the Shore D scale using a hardness tester purchased from Electromatic Equipment Co., Inc. Softer pads (pads with lower hardness) exhibited higher removal rates, which is intuitively apparent because the softer pads correspond to a larger contact area between the pad and the Mo surface.
[0074] Table 3: Effect of Pad Changes on Mo Removal Rate
[0075]
[0076] Slurry F and slurry G are made of the same particles, at the same composition pH, but with different solid loadings, namely 5% by weight and 1% by weight, respectively.
[0077] Example 4
[0078] Slurry G was further modified by adding an oxidant to investigate the increased removal rate due to the oxidative chemistry between Mo and the oxidant. Hydrogen peroxide was added as the oxidant at a concentration of 0.1%. A 100% increase was observed after the addition of the oxidant. However, the SER was significantly higher compared to the 'abrasive alone' formulation. Various corrosion inhibitors (CI 1 to 8, dodecyltrimethylammonium bromide (1), glycine (2), benzotriazole (3), imidazoline oleate (4), dialkyl sulfonate (5), ammonium lauryl sulfate (6), benzalkonium chloride (7), benzyl chloride (8)) were used. The room temperature SER data at the operating pH in the presence of these inhibitors and a 0.1% oxidant concentration are shown in Table 4. Two inhibitors, CI-7 and CI-8, showed the greatest performance when the SER value was below the detection limit.
[0079] Table 4: SER and RR data in the presence of oxidants and corrosion inhibitors
[0080]
[0081] Example 5
[0082] After observing a significant decrease in SER values in the presence of slurries G7 and G8, the formulation of slurry G was further modified to investigate a further increment in the removal rate by introducing a Fenton catalyst (e.g., ferric(III) nonahydrate) to induce catalytic activity similar to the Fenton reaction. 140 ppm of the catalyst was added to the formulation in Example 5, and the Mo removal rate and SER were tested. The removal rate increased by approximately 20% upon addition of the catalyst without compromising corrosion inhibition efficiency. SER values for various oxidant concentrations with 140 ppm of the catalyst are recorded in Table 5.
[0083] Table 5: Effects of Catalyst Addition and Corrosion Inhibition Efficiency
[0084]
[0085] Examples of B-ruthenium polishing
[0086] Experimental setup:
[0087] All removal rate experiments were performed on a Pioneer Automet 250 benchtop polisher using 1.25” x 1.25” ruthenium PVD evaporation plates at a platform speed of 100 RPM and a head speed of 60 RPM. A flow rate of 30 mL / min was maintained. Data were generated on a blanket-type SUBA-1200 polishing pad. Removal rates were measured using a five-point characterization method with a four-point probe (ResMap).
[0088]
[0089] Table 6: Removal rates at 3 psi DF and pH 11.5 for different abrasives (excluding other chemicals)
[0090] These experiments show that aluminum-coated titanium dioxide particles have a catalytic reaction with the ruthenium surface, forming RuO. x - The passivation layer is easily removed by abrasive and pad friction.
[0091] For the next set of experiments, aluminum-coated titanium dioxide abrasives with a size of ~200 nm and a solid load of 2.5% were used.
[0092]
[0093]
[0094] Table 7: Removal rates of different oxidants at 3 psi DF and different pH values
[0095] The above data reflect processes above pH 6; below pH 6, toxic RuO4 (ruthenium tetroxide) may form. Furthermore, pad staining decreases with increasing pH; it decreases sharply above pH 9, and staining is barely observed at pH 12.5. This can be attributed to the formation of soluble RuO4 at higher pH levels. - / RuO2 - Ions, not RuO2 and RuO4.
[0096] aspect
[0097] In a first aspect, the present invention provides a composition comprising:
[0098] Liquid carrier;
[0099] Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina or amorphous silica to provide coated titanium dioxide abrasive particles;
[0100] The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and
[0101] Corrosion inhibitor.
[0102] In a second aspect, the present invention provides a composition of the first aspect, wherein the coated titanium dioxide abrasive particles are coated with alumina.
[0103] In a third aspect, the present invention provides a composition of the first or second aspect, wherein the coated titanium dioxide abrasive particles are coated with amorphous silicon.
[0104] In a fourth aspect, the present invention provides a composition of any one of the first, second, or third aspects, wherein the corrosion inhibitor is a cationic surfactant.
[0105] In a fifth aspect, the present invention provides a composition of any one of the first to fourth aspects, wherein the corrosion inhibitor is selected from benzalkonium chloride and benzalkonium bromide.
[0106] In a sixth aspect, the present invention provides a composition of any one of the first to fifth aspects, wherein the pH is from about 2 to about 5.
[0107] In a seventh aspect, the present invention provides a composition of any one of the first to sixth aspects, said composition further comprising at least one oxidizing agent.
[0108] In an eighth aspect, the present invention provides a composition of the seventh aspect, wherein the oxidant is selected from hydrogen peroxide and periodic acid.
[0109] In a ninth aspect, the present invention provides a method for chemically and mechanically polishing a substrate comprising a surface including at least one transition metal, the method comprising:
[0110] The substrate is brought into contact with the composition, the composition comprising:
[0111] Liquid carrier;
[0112] Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina or amorphous silica to provide coated titanium dioxide abrasive particles;
[0113] The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and
[0114] Corrosion inhibitors;
[0115] To move the composition relative to the substrate; and
[0116] The substrate is scraped to remove a portion of the surface comprising at least one transition metal.
[0117] In a tenth aspect, the present invention provides a method of the ninth aspect, wherein the surface comprises molybdenum.
[0118] In an eleventh aspect, the present invention provides a method of the ninth aspect, wherein the surface comprises ruthenium.
[0119] In a twelfth aspect, the present invention provides a method of the ninth, tenth, or eleventh aspect, wherein the pH is from about 2 to about 5.
[0120] In a thirteenth aspect, the present invention provides a method of any one of the ninth to twelfth aspects, wherein the coated titanium dioxide abrasive particles are coated with alumina.
[0121] In a fourteenth aspect, the present invention provides a method of any one of the ninth to thirteenth aspects, wherein the coated titanium dioxide abrasive particles are coated with amorphous silicon.
[0122] In a fifteenth aspect, the present invention provides a method of any one of the ninth to fourteenth aspects, wherein the corrosion inhibitor is selected from benzalkonium chloride and benzalkonium bromide.
[0123] In a sixteenth aspect, the present invention provides a method for chemically and mechanically polishing a substrate comprising a surface including at least one of molybdenum or ruthenium, the method comprising:
[0124] The substrate is brought into contact with the composition, the composition comprising:
[0125] Liquid carrier;
[0126] Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina or amorphous silica to provide coated titanium dioxide abrasive particles;
[0127] The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and
[0128] Corrosion inhibitor.
[0129] To move the composition relative to the substrate; and
[0130] The substrate is scraped to remove a portion of the surface containing at least one of molybdenum or ruthenium.
[0131] In a seventeenth aspect, the present invention provides a kit comprising a component selected from components a, b, and c as defined in any one of the first to eighth aspects in one or more containers.
[0132] Having described several illustrative embodiments of this disclosure, those skilled in the art will readily understand that other embodiments may be made and used within the scope of the appended claims. Many advantages of this disclosure covered in this document have been mentioned in the foregoing description. However, it should be understood that this disclosure is illustrative in many respects only. The scope of this disclosure is, of course, defined in the language expressed in the appended claims.
Claims
1. A composition for chemically and mechanically polishing a substrate comprising a surface including molybdenum, said composition comprising: Liquid carrier; Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina to provide coated titanium dioxide abrasive particles, wherein the coated titanium dioxide abrasive particles are coated with alumina. The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and Corrosion inhibitors, wherein the pH is approximately 2 to approximately 5.
2. The composition according to claim 1, wherein the corrosion inhibitor is a cationic surfactant.
3. The composition according to claim 2, wherein the corrosion inhibitor is selected from benzalkonium chloride and benzalkonium bromide.
4. The composition according to claim 1, further comprising at least one oxidizing agent.
5. The composition according to claim 4, wherein the oxidant is selected from hydrogen peroxide and periodic acid.
6. A method for chemically and mechanically polishing a substrate comprising a surface including at least one transition metal, the method comprising: The substrate is brought into contact with the composition, the composition comprising: Liquid carrier; Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina to provide coated titanium dioxide abrasive particles, wherein the coated titanium dioxide abrasive particles are coated with alumina. The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and Corrosion inhibitor, wherein the pH is from about 2 to about 5; To move the composition relative to the substrate; and The substrate is scraped to remove a portion of the surface comprising at least one transition metal.
7. The method of claim 6, wherein the surface comprises molybdenum.
8. The method of claim 6, wherein the surface comprises ruthenium.
9. The method according to claim 6, wherein the corrosion inhibitor is selected from benzalkonium chloride and benzalkonium bromide.
10. A method for chemically and mechanically polishing a substrate comprising a surface including at least one of molybdenum or ruthenium, the method comprising: The substrate is brought into contact with the composition, the composition comprising: Liquid carrier; Titanium dioxide abrasive particles, wherein the particles are at least partially coated with alumina to provide coated titanium dioxide abrasive particles, wherein the coated titanium dioxide abrasive particles are coated with alumina. The coated titanium dioxide abrasive particles have an average diameter of about 50 nm to about 250 nm; and Corrosion inhibitor, wherein the pH is from about 2 to about 5; To move the composition relative to the substrate; and The substrate is scraped to remove a portion of the surface containing at least one of molybdenum or ruthenium.
Citation Information
Patent Citations
Composition for chemical mechanical polishing and manufacturing method thereof, and polishing method
JP2021019111A
Abrasive grain, and chemical mechanical polishing composition
JP2021027223A
KR20200123648A